Impulsiveness in Reactive Dieters: Evidence From Delay Discounting in Orthodontic Patients - Zhang, Wu; Mai, Chunmiao; Chen, Hongmin; Zhang, Huijun (Frontiers in Human Neuroscience, 2018)
ABSTRACT Introduction: Researchers have made efforts to distinguish the behavioral differences and underlying mechanisms that explain the various possible outcomes of dieting (success, failure and relapse). Although extensive research has demonstrated that eating behavior and individual impulsiveness are closely related to subjective appetite and decision making, very few studies have investigated how subjective and appetite impulsiveness is affected by reactive dieting. Methods: In the present study, we utilized the Power of Food Scale (PFS) and the intertemporal choice task and to examine subjective appetite and impulsivity of decision making in orthodontic patients. As a result of their orthodontic devices and the subsequent pain and discomfort caused by eating, these patients become reactive dieters. In order to explore the dynamic influence of orthodontic treatment on appetite and impulsiveness, we collected data for both patients and control participants across three testing sections. We also computed a regression model for further exploration in explaining how potential factors contributed to different choices. Results: We found that the orthodontic group scored significantly lower in PFS than the control group, which indicated a suppression in appetite. Besides, reward and waiting time were significant factors in computational perspective. Moreover, although patients showed a bias in choosing smaller, immediate reward options, they exhibited a decrease in the delay discounting rate as treatment progressed. These findings confirm that subjective appetite and impulsiveness were inhibited due to reactive dieting.